Implementasi Model Pembelajaran Kewirausahaan Berbasis Kompetensi dan Pengalaman untuk Menciptakan Wirausaha Baru pada Siswa Smk Yogyakarta - Hari Rachmadi (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2015)
The strength of character to be entrepreneurs, the strength of the motivation to start and own a business, entrepreneurial perception, the seriousness of the effort to seek opportunities and take advantage of business opportunities and perseverance run Synchronize employment policies, business and academia showed the strategic in building an entrepreneurial culture both in shaping new entrepreneurs, as well as for survival both businesses large and small to create the nation’s economic added value. In addition, the study empires show that entrepreneurship program has a positive effect on the development of entrepreneurial attributes of individual, self-reliance, raise awareness of entrepreneurship as a career option and instil a positive attitude towards entrepreneurship.Opportunities offered competency-based model of entrepreneurial learning and experience (competence-base and experience entrepreneurship learning - CBE2L) are implemented systematically, challenges and implications for policymakers, employers and types discuss in relation to relevant theoretical perspectives. Key implications CBE2L models. is to encourage learning program with policy and institutional commitment of resources, teachers who have the knowledge and experience of entrepreneurship and disseminate issues of education in strengthening involvement entrepreneurial culture among students.